A functional neuregulin-1 gene variant and stressful life events: Effect on drug use in a longitudinal population-representative cohort study. (January 2017) - Vaht, Mariliis; Laas, Kariina; Kiive, Evelyn; Parik, Jüri; Veidebaum, Toomas; Harro, Jaanus
Background: The neuregulin 1 gene is a susceptibility gene for substance dependence. A functional polymorphism (SNP8NRG243177/rs6994992; C/T) in the promoter region of the brain-specific type IV neuregulin-1 gene ( NRG1 ) has been associated with psychiatric disorders (e.g. schizophrenia and bipolar disorder) that often present higher odds of smoking, alcohol and illicit drug use. This study assessed the association of the NRG1 genotype with drug use and possible interaction with stressful life events (SLEs). Methods: The database of the Estonian Children Personality Behaviour and Health Study (beginning in 1998) was used. Cohorts of children initially 9 years old ( n =583; followed up at 15 and 18 years) and 15 years old ( n =593; followed up at 18 and 25 years) provided self-reports on alcohol, tobacco and illicit substance use and SLEs. Psychiatric assessment based on DSM-IV was carried out on the older birth cohort at age 25 to assess the lifetime presence of substance use disorders. NRG1 rs6994992 was genotyped in all participants by TaqMan® Pre-Designed SNP Genotyping Assay on the Applied Biosystems ViiA™ 7 Real-Time PCR System. The minor (T) allele frequency was 0.37. Results: NRG1 rs6994992 C/C homozygotes, especially those who had experienced more SLEs, were more likely to develop alcohol use disorders by young adulthood, were generally more active consumers of tobacco products, and had more likely used illicit drugs. In T allele carriers, SLEs had a negligible effect on substance use. Conclusions: In humans, NRG1 genotype is associated with substance use, and this relationship is moderated by adverse life events, with a gain-of-function allele being protective.